SKIN CANCER AND MELANOMA IN THE AMUR REGION OF THE FAR EASTERN FEDERAL DISTRICT - V. P. Gordienko; N. A. Tovbik; E. V. Klimenko (Сибирский онкологический журнал)
The paper analyzes the rates of cancer morbidity and mortality from 1998 to 2014 in the Amur region. During the study period, the incidence of skin cancer increased significantly with increasing the crude incidence rate by 60.7 %, and standardized incidence rate by 19.5 %. For melanoma, the corresponding rates were 87.3 % and 43.3 %, respectively. In contrast to the incidence rates, the absolute, crude and age-standardized mortality rates decreased. The analysis of age-adjusted melanoma skin cancer incidence rates indicated that the highest incidence was observed in the age group of 75 years and older. Early skin cancer (stage I–II) was registered in 95.4 % of patients, and early melanoma in 68.8 %. The mortality rates in the first year after diagnosis increased by 0.7 % in patients with skin cancer and decreased by 5 % in patients with melanoma. The number of patients who followed up for 5 year and more significantly increased. The role of primary cancer care in the region was estimated.